Metal Accumulation Properties of Eight Traditionally Utilized Nutritional Plants and Their Potential as Suitable Crops for Cultivation on Acidic Soils of the Northern Province Uíge, Angola - Christin Baumgärtel; Thea Lautenschläger; Mazekana H. G. Panzo; Francisco Afonso; Christoph Neinhuis; Karl-Heinz Feger (Applied Sciences, 2022)
High metal contents of acidic soils from sub-Saharan Africa often prevent the cultivation of crops and lead to a low livestock yield. The carbohydrate rich diet of the Angolan population is low in minerals and vitamins, resulting in various deficiency syndromes and a high child mortality rate. Eight traditionally utilized plants (Anisophyllea quangensis, Annona stenophylla subsp. cuneata, Canarium schweinfurthii, Eugenia malangensis, Landolphia lanceolata, Raphionacme madiensis, Tristemma mauritianum, Vitex madiensis subsp. madiensis) with nutritional value for the Angolan population were analyzed for their soil and growing conditions. The species are adapted to the local conditions and can serve as crops for the unfavorable soils of the province Uíge. Chemical and physical characteristics of the uppermost soil (0–5 cm) and in 30 cm depth were analyzed. The plant-available macro-and micronutrients were determined using Mehlich 3 extraction. Data are completed with leaf tissue analyses, examining the uptake of minerals. As aluminum (Al) and manganese (Mn) are plant-available in high amounts, local plants evolved mechanisms dealing with those metals. These Al accumulators with foliar contents above 1000 mg/kg are Anisophyllea quangensis (7884 mg/kg), Landolphia lanceolata (6809 mg/kg), Tristemma mauritianum (4674 mg/kg), and Eugenia malangensis (13,989 mg/kg). All four species bear edible fruits with nutritional potential. The domestication and commercialization of those plants seem to be promising, utilizing local soils without expensive amelioration techniques.